Reflecting on educational leadership during COVID-19 : experiences of Finnish higher education leaders and lessons for future crises and emergencies - Perkins, Marc C. (2023)
Crisis leadership research as a field has a long history in business, but less so in education, especially higher education. Existing educational crisis leadership research has highlighted the importance of adaptive leadership, collaboration, communication, complex decision making, context, and well-being. The SARS-CoV-2 virus’s arrival in 2019 caused a multi-year global crisis. Unfortunately, most crisis leadership pre-COVID-19 focused on acute, short-term crises, which raises the questions: how did university leadership manage this chronic crisis, what lessons can be learned from these experiences, and how does existing crisis leadership theory align with these experiences?